Development of interactive learning media through 2D animated video in Indonesian language learning - Zhafran Afif Nurdiyansah; Berlilana Berlilana (Journal of Educational and Learning Studies, 2025)
The development and advancement of technology play a crucial role in various fields, including education. Learning media holds significant importance in the teaching and learning process. Furthermore, the use of learning media can also have positive psychological effects on students. As we know, first-grade students are still at a stage where it can be challenging for teachers to provide explanations that they can fully comprehend. One example is at MI Muhammadiyah Kalilandak, where many students still struggle with reading, especially in the first grade. Since fluent reading is essential, the use of learning media that can support these students is necessary, such as through 2D animated videos. With the inclusion of videos equipped with animation, text, and music, it is hoped that the students will be more motivated in their learning. Therefore, this research will focus on the creation of 2D animated videos to enhance the reading abilities of the students.